2020
DOI: 10.3892/ijmm.2020.4464
|View full text |Cite
|
Sign up to set email alerts
|

Ligustrazine ameliorates acute kidney injury through downregulation of NOD2‑mediated inflammation

Abstract: Ligustrazine has been used to alleviate clinical acute kidney injury (AKI); however, the underlying molecular mechanisms are poorly understood. In order to further elucidate the molecular mechanism underlying its occurrence, the role of nucleotide-binding oligomerization domain-containing 2 (NOd2) in AKI was investigated in the present study, and the results indicated that ligustrazine exerts an important protective effect against AKI in vivo by inhibiting the upregulation of NOd2 expression and reducing apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…For example, IL-6, MCP-1, and TNF-α levels were upregulated by H. pylori infection in GES-1 cells (20). In the present study, H. pylori infection enhanced the mRNA and protein expression levels of IL-6/8, MCP-1, and TNF-α in GES-1 cells, which were consistent with a previous study, showing that ligustrazine reduced inflammation in the kidney cells postischemia/reperfusion injury with decreased levels of IL-6, MCP-1, and TNF-α (21). Besides, our results also confirmed that ligustrazine attenuated H. pylori-induced increased levels of IL-6/8, MCP-1, and TNF-α in GES-1 cell line, suggest-ing its anti-inflammatory effect on H. pylori-induced gastritis.…”
Section: Discussionsupporting
confidence: 93%
“…For example, IL-6, MCP-1, and TNF-α levels were upregulated by H. pylori infection in GES-1 cells (20). In the present study, H. pylori infection enhanced the mRNA and protein expression levels of IL-6/8, MCP-1, and TNF-α in GES-1 cells, which were consistent with a previous study, showing that ligustrazine reduced inflammation in the kidney cells postischemia/reperfusion injury with decreased levels of IL-6, MCP-1, and TNF-α (21). Besides, our results also confirmed that ligustrazine attenuated H. pylori-induced increased levels of IL-6/8, MCP-1, and TNF-α in GES-1 cell line, suggest-ing its anti-inflammatory effect on H. pylori-induced gastritis.…”
Section: Discussionsupporting
confidence: 93%
“…Chen et al found that TMP could reduce renal I/R damage by enhancing autophagy, indicated by increased LC3-II/I ratio and Beclin-1 in kidney tissue ( Chen et al, 2020 ). Another study found that TMP reduced inflammation in renal I/R injury and was related to the activation of autophagy ( Jiang et al, 2020 ). Interestingly, in a study on CI-AKI, we found that the mechanism by which TMP protected the kidney from contrast agent damage was partly related to the inhibition of autophagy ( Gong et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…All other procedures were the same. In the I/R+TMP group, TMP hydrochloride was given immediately after reperfusion (40 mg/kg, 6-h interval) by intraperitoneal injection ( 23 ). At 24 h after the PBS cardiac perfusion, kidney tissues were taken; some tissues were stored at −80°C for protein and reverse transcription-quantitative (RT-q) PCR detection, while some tissues were fixed with 4% paraformaldehyde at 4°C for 24 h, embedded in paraffin, and sliced for morphological detection.…”
Section: Methodsmentioning
confidence: 99%